Pengembangan Game Simulasi Pembuatan SKCK Sebagai Media Pembelajaran Menggunakan Metode MDLC - Arisandi, Heldi; Wulansari, Tina Tri (STMIK Banjarbaru, 2024)
The lack of public understanding regarding the process of obtaining a Police Certificate (SKCK) forms the core issue identified. The public often experiences confusion or difficulty in following SKCK procedures due to a lack of understanding of police regulations. Therefore, this research aims to address this issue by developing an educational game that can be run on Android devices. Utilizing the Multimedia Development Life Cycle (MDLC) development method, a game titled